Combination therapy with preoperative embolization and en block laminectomy using thread saw for spinous process solitary fibrous tumor: A case report - Tomohiro Yamada, MD; Tomohiko Hasegawa, MD, PhD; Yoji Shido, MD, PhD; Yu Yamato, MD, PhD; Go Yoshida, MD, PhD; Tatsuya Yasuda, MD, PhD; Tomohiro Banno, MD, PhD; Hideyuki Arima, MD, PhD; Shin Oe, MD, PhD; Hiroki Ushirozako, MD, PhD; Koichiro Ide, MD; Yuh Wanatabe, MD; et al. (Radiology Case Reports, 2020)
Solitary fibrous tumors are rare mesenchymal neoplasms with highly recurrence rates after intratumor resection. We report 2 cases of solitary fibrous tumors treated with combination therapy with embolization and en bloc laminectomy using thread saw. To the best of our knowledge, this is the first such report. In the 2 cases, the hypervascular tumors were located in the spinal process and infiltrating the multifidus. Preoperative embolization was useful for decreasing intraoperative bleeding, and using thread saw was an ideal technique for deciding the cut surface height of the pedicle to achieve gross total resection.